2013
DOI: 10.1038/aja.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, an activator of SIRT1, restores erectile function in streptozotocin-induced diabetic rats

Abstract: The high incidence of erectile dysfunction (ED) in diabetes highlights a need for effective treatment strategies. Resveratrol, an activator of silent information regulator 2-related enzymes 1 (sirtuin1, SIRT1), has received attention for its valuable effects in cancer, neurodegenerative diseases, longevity and cardiovascular disease. To explore the effects of resveratrol in diabetes-induced ED, resveratrol was administered to rats with streptozocin (65 mg kg 21 )-induced diabetes. Erectile function, cavernous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 43 publications
7
56
0
2
Order By: Relevance
“…They also used tissue levels of TBARS as an indicator of oxidative stress. Yu et al [29] studied SOD activity and levels of TBARS as a measure of oxidative stress in the corpus cavernosum. SOD is a major cellular defense against the superoxide and TBARS is a reactive aldehyde and one of the many reactive electrophile species that can cause the toxic stress in cells.…”
Section: Discussionmentioning
confidence: 99%
“…They also used tissue levels of TBARS as an indicator of oxidative stress. Yu et al [29] studied SOD activity and levels of TBARS as a measure of oxidative stress in the corpus cavernosum. SOD is a major cellular defense against the superoxide and TBARS is a reactive aldehyde and one of the many reactive electrophile species that can cause the toxic stress in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting these pathways for therapeutic intervention may be achieved by increasing activity of upstream regulators of biogenesis such as the TOR pathway, Sirtuins, NAD+ boosters and AMPK [117][118][119] or by increasing activity of downstream effectors of biogenesis such as TFAM, PGC-1α and NRF-1 [120]. The most understood pharmacological agents from these pathways are the SIRT1 doi: 10.7243/2052-6946-1-8 agonists SRT1720 and SRT 2104 both of which have been shown to increase lifespan in mice [121]. Future studies into SIRT1 agonists may lead to new pharmacological treatments for mitochondrial disease but no current clinical study has shown a positive effect in human hosts.…”
Section: Gene Based Therapeutic Approachesmentioning
confidence: 99%
“…-↑ ↓ Oxidative stress in corpus cavernosum, ↓ corporal tissue apoptosis and ↑ penile erectile function (Yu et al, 2013). Rutin (flavonoid) 50 and 100mg/kg/day, et al, 2015).…”
Section: Natural Products With Pre-testicular (Hpg-axis) Beneficial Ementioning
confidence: 99%